Pendampingan UMKM dalam Meningkatkan Kualitas Sumber Daya Manusia dan Pendapatan Keluarga - Maya Yusnita; Novita Herlissha; Reniati Reniati; Nanang Wahyudin; Padlun Fauzi; Khadijah Khadijah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
Karya Makmur Village  is one of the villages in the Pemali District Bangka Regency Bangka Belitung Islands Province. The problem of Karya Makmur Village that the knowledge of MSMEs actors is still quite low regarding MSME development strategies both in terms of Human Resources (HR), marketing and  finance.  In addition, MSMEs actors also do not have product licensing legality such as Halal Certification and Business Identification Number (NIB). The method of  the program are outreach, education, training and mentoring. The stages of the activity consist of preparation, implementation,  mentoring  and  evaluation.  The  implementation  of the program has provided understanding, motivation, competency and skills in  MSMEs development both in  the fields of Human Resources (HR), Marketing, Finance and product licensing (Halal Certification and  NIB).  This activity will be periodically monitored and evaluated in order to maintain the sustainability of the program.